POTENSI ANDROGRAFOLID, DEOKSIANDROGRAFOLID, NEOANDROGRAFOLID SEBAGAI ANTIATEROSKLEROSIS PADA CASPASE-1: STUDI IN SILICO - Ugrasena, Putu Yudha; Puspita Sari, Dyah Ratna Ayu; Indraswari, Putu Ika Indah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Atherosclerosis is a vascular pathological condition characterized by active, chronic, progressive inflammation and plaque formation in the arterial walls Interleukin 1-beta (IL-1β) cytokine influences every stage of atherosclerosis, from destroying monocytes and other immune cells to forming plaques. Caspase-1 protein plays a role in activating the inflammatory cytokine Pro-Interleukin-1 Beta (Pro IL-1β) to IL-1β. One of the plants that has the potential to treat atherosclerosis is Andrographis paniculata. Andrographolide and its analogs, such as neoandrographolide and deoxyandrographolide, are the main bioactive compounds with various pharmacological activities. This study aimed to screen the activity of the compounds through the description of the stability of the compounds in protein caspase-1. This type of research was an in-silico exploratory study of the caspase-1 protein (PDB ID: 1RWK), with compound preparations, protein preparations, validating the molecular docking method to docking andrographolide neoandrografolid and deoksiandrografolid compounds on the target protein. The compounds has an affinity for the target protein with binding energy values ​​of -5.95 kcal/mol, -6.02 kcal/mol, and -6.81 kcal/mol respectively, which are smaller than the native ligand -4.77 kcal/mol. Docking results show that andrographolide, neoandrografolid, and deoxyandrografolid can potentially inhibit caspase-1, which activates the pro-inflammatory cytokine IL-1β in atherosclerosis.